2015
DOI: 10.1508/cytologia.80.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Micro-morphological and Karyomorphological Studies in Three Mulberry Varieties (<i>Morus</i> spp.)

Abstract: Summary This article reveals the micro-morphology and karyomorphological characters of three mulberry varieties, namely, Thysong, S 41 and Morus multicaulis. Stomatal frequency, somatic chromosome number, ploidy level and karyotype analysis were studied for these varieties. Thysong is diploid with 2n=28, S 41 is triploid with 2n=42 and Morus multicaulis is uneuploid with 2n=30 regarding somatic chromosomes numbers. The somatic chromosome length ranges from 1.26 to 2.83 μm, whereas the arm ratio ranges from 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The basic chromosome number (x = 14) of mulberry was proposed a long time ago 6 , 7 . This idea has been widely cited in later studies 8 – 10 . Cytogenetic researchers, Das 11 and Datta 12 , doubted this theory based on their observations of secondary associations in a few varieties of Morus indica .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The basic chromosome number (x = 14) of mulberry was proposed a long time ago 6 , 7 . This idea has been widely cited in later studies 8 – 10 . Cytogenetic researchers, Das 11 and Datta 12 , doubted this theory based on their observations of secondary associations in a few varieties of Morus indica .…”
Section: Introductionmentioning
confidence: 82%
“…Various studies have shown that mulberry contains abundant polyploid levels and similar chromosome morphologies 4 , 8 . These studies were focused on chromosome counting and chromosome behaviors during the meiotic phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytogenetical and karyotypic studies have revealed variations of chromosomes in size, morphology, and number in various clades of plant and animal species (Al-Dakan and Al-Saleh 2015, Al-Qahtani et al 2014, Arslan and Zima 2014, Bagane et al 2014, Çakmak and Koca 2014, Deshpande et al 2014, El-Esawi and Sammour 2014, Gholave et al 2014, Haroun and Alotaibi 2015, Jantarat et al 2014a, Kaewmad et al 2014, 2014c, Kantek et al 2015, Kasiroek et al 2014, Kaur and Singhal 2015, Khakhong et al 2014, Kumar et al 2015, Kumar et al 2014, Li et al 2015, Martin et al 2015, Miura and Iwatsubo 2014, Parai and Mukherjee 2014, Park 2015, Patawang et al 2014a, Phimphan et al 2015, Pierozzi and Baroni 2014, Pinthong et al 2014, Qumsiyeh et al 2014, Rezaei et al 2014, Samanta et al 2015, Sato et al 2015, Tahami et al 2014, Venkatesh and Munirajappa 2015, Venkatesh et al 2014, Walia et al 2015. Cytogenetical techniques including banding methods and FISH have revealed the evolutionary process in structural and number changes of chromosomes (Lombello and Pinto-maglio 2014…”
mentioning
confidence: 99%